The impact of methamphetamine on psychosocial variables in patients from Iraq - Abbass, Marwah; Al-Hemiary, Nesif; Sahib, Hayder B. (Frontiers in Psychiatry, 2024)
Background The current work reviews the psychosocial factors associated with different urinary methamphetamine concentration levels. Methods From April to November 2023, 243 participants from Baghdad’s Al-Ataa Hospital were the subjects of a cross-sectional descriptive analysis study. We included 73 patients in this study. Result The urinary methamphetamine concentration levels were from 3 to 92,274 ng/ml, with a mean ± SD of 10,873.6 ± 18,641. Patients diagnosed with major depression disorder exhibited higher scores on GHQ-30, UCLA, MOAS, and BDI-II with a significant P-value of 0.0001, 0.001, 0.0001, and 0.0001, consequently with an effect size of 0.015, 0.001, 1.05, and 3.24, respectively. Conclusions The multi-screening test can produce a false positive. It frequently interferes with other drugs, especially antidepressants. This will result in patients being stigmatized and accused. On the other hand, those who accidentally come into contact with crystal smoke will experience the same withdrawal symptoms as the addicted patients. Their urinary methamphetamine level (titer) could have negative results. Urinary methamphetamine levels should be zero in healthy patients. In this situation, screening tests, expert opinion, and urine methamphetamine testing are strongly recommended.